Ontologi Ilmu Pengetahuan - Ermida Ermida; Ardimen Ardimen (Journal on Education, 2023)
Ontology is a science that examines what is the nature of science or scientific knowledge which is popularly known by many people as science, what is the nature of rational truth or deductive truth and empirical reality that cannot be separated from science's perception of what and how. The ontology of science limits itself to scientific studies that humans can think about rationally and can observe through the five human senses. Meanwhile, the study of objects of study that are within the limits of pre-experience (such as human creation) and post-experience (such as heaven and hell) becomes an ontology of other knowledge outside of science. In language, ontology comes from the Greek word origin is "Ontos" and "Logos". Ontos is "that which exists" while Logos is "knowledge". Simply put, ontology is the science that talks about what exists. In terms, ontology is a branch of philosophy that deals with the nature of life about an existence which includes the existence of everything that exists and that may exist. And do not mix up the truth with falsehood and (do not) hide the truth while you know it. (QS. Al-Baqarah Verse 42) Ontology basically talks about the nature of "existing" science, the nature of knowledge objects, and the nature of the subject-object relationship of science. How science is viewed ontologically, the discussion is that ontology examines, analyzes knowledge based on whether knowledge really exists or does not exist. For example in Islamic Education Management, ontologically the discussion is focused on Islamic Education Management does it really exist or not, not only the study program but actually the knowledge taught in it is actually no different from Education Management in general.